Ring-based bandwidth dimensioning in SDH networks - Owen, Henry L. (Computer communications, 1996)
Determining the bandwidth requirements for Synchronous Digital Hierarchy (SDH) networks requires examination of the network topology, the equipment functionality in the network, the switching algorithms, the protection methodology, and the traffic statistics for each of the multi-rate bandwidths to be transmitted in the network. The complexity of this type of analysis requires a computer aided design algorithm. A bandwidth routing algorithm for SDH networks which include unidirectional and bidirectional ring topologies in either a centralized or distributed traffic switching environment is presented. Several simple network examples are provided so the algorithm may be followed ‘in action’. The algorithm is then demonstrated on an actual European metropolitan network to determine the bandwidth requirements for that network. Pseudo-code for the algorithm is presented in an appendix.